2019
DOI: 10.1038/s41421-019-0137-3
|View full text |Cite
|
Sign up to set email alerts
|

More than one antibody of individual B cells revealed by single-cell immune profiling

Abstract: Antibodies have a common structure consisting of two identical heavy (H) and two identical light (L) chains. It is widely accepted that a single mature B cell produces a single antibody through restricted synthesis of only one VHDJH (encoding the H-chain variable region) and one VLJL (encoding the L-chain variable region) via recombination. Naive B cells undergo class-switch recombination (CSR) from initially producing membrane-bound IgM and IgD to expressing more effective membrane-bound IgG, IgA, or IgE when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 44 publications
(46 reference statements)
5
41
0
Order By: Relevance
“…Second, PTEC-derived IgG had conservative V(D)J rearrangements, showing that VH1-24/DH2-15/JH4 was predominant in more than 10% of PTECs, 10 pairs of single PTECs from different individuals and 5 pairs of single PTECs from the same individual shared the same V H DJ H rearrangements. All these are considered impossible in such a small number of B cells, and primer bias was excluded as the diversity of V(D)J rearrangements was proven in PBMCs (Table S6) or single B cells 24 . The phenomenon of conserved IgG characteristics has also been described in other non-B cells, such as human epithelial cancer cells 25 or endothelial cells 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, PTEC-derived IgG had conservative V(D)J rearrangements, showing that VH1-24/DH2-15/JH4 was predominant in more than 10% of PTECs, 10 pairs of single PTECs from different individuals and 5 pairs of single PTECs from the same individual shared the same V H DJ H rearrangements. All these are considered impossible in such a small number of B cells, and primer bias was excluded as the diversity of V(D)J rearrangements was proven in PBMCs (Table S6) or single B cells 24 . The phenomenon of conserved IgG characteristics has also been described in other non-B cells, such as human epithelial cancer cells 25 or endothelial cells 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of the single-cell suspension was counted and adjusted to 1000 cells/μl for sorting 7000 cells. All remaining procedures, including library construction, were performed according to the manufacturer's standard protocol described in Shi's work 24 . We used the Cell Ranger software pipeline (version 3.0.0) to demultiplex cellular barcodes and map reads to the genome.…”
Section: × Library Preparation and Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this result is limited to single-locus gene changes. Studies have shown that IGH rearrangement can affect related genes and trigger the autocrine mechanism of tumors [32] , leading to disease progression [33] . This may be the cause of the increased tumor load that leads to a decrease in the ADC value.…”
Section: Discussionmentioning
confidence: 99%
“…On antigenic exposure, 'baseline' (resting-state) antibodies with sufficiently complementary binding sites to an antigen surface epitope are positively selected. The corresponding parent B cells subsequently migrate to the marginal zone of the lymph nodes, where intentional mutations are introduced to their sequence and only the highest-affinity binders survive in the competition for cognate T-helper cells (2). Therefore, sequencing antibody repertoires before and during an immune response (e.g.…”
Section: Introductionmentioning
confidence: 99%